PENATALAKSANAAN FISIOTERAPI PADA DELAY DEVELOPMENT DENGAN HALLIWICK DAN NEURO DEVELOPMENT TREATMENT UNDERWATER IN YPAC SURAKARTA - Puji Wahyuningrum; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Delay Development is a delay in growth and development of children in the form of significant lagging in physical activities including crawling, sitting, standing and walking, cognitive abilities, behaviors, emotions or social development in children when compared to normal children his age. Problems that arise in Delay Development conditions namely postural development hypotonic, growth delay motoric development, postural imbalance and functional limitation. Objective Halliwick to improve bodily functions and maintain balance in water and the Neuro development treatment underwater aims to improve the tone of posture in water. This research was conducted at YPAC Surakarta with a descriptive analytic the research design used is a case study design. The subjects of this study were patients with Delay development conditions who would be given physiotherapy interventions using the Halliwick and Neuro development treatment underwater methods. Methods of data collection and data analysis using the Heteroanamnesis. The research instrument consisted of an examination of Growth and Development assessed 4 aspects, namely: social social, fine motor skills, abusive language and Examination of Motor Muscle Strength with MMT, examination of spontaneous motion reaction reflexes with empty reflexes, Sensory Examination consisting of Visual, hearing, aroma, taste, touch, touch, proprioception and vestibular and Examination of Functional Activity Ability with GMFM. Results After 5 treatment, the following results were obtained: (1) There was an increase in DDST, (2) Increased muscle strength, (3) There was no increase in reflexes, (4) There is a sensory increase in vestibular, (5) There is an increase in functional ability T1=63% to 68%. Conclusion From this research that physiotherapy modality with Halliwick and Neuro development treatment underwater can reduce problems in Delay development conditions. Suggestion Patients are asked to exercise regularly at home so that there is a significant increase.